The Properties of Thermosensitive Zwitterionic Sulfobetaine NIPAM-co-DMAAPS Polymer and the Hydrogels: The Effects of Monomer Concentration on the Transition Temperature and Its Correlation with the Adsorption Behavior - Eva Oktavia Ningrum; Agus Purwanto; Galuh Chynintya Rosita; Asep Bagus (Universitas Gadjah Mada, 2020)
The properties of N-isopropylacrylamide copolymerized with N,N-dimethyl(acrylamidopropyl)ammonium propane sulfonate [poly(NIPAM-co-DMAAPS)] prepared with various monomer ratios such as transition temperature, molecular structure, viscosity were systematically investigated in water and Zn(NO3)2 solution. Poly(NIPAM-co-DMAAPS) in water and Zn(NO3)2 solution exhibited a phase transition with a lower critical solution temperature (LCST). The higher ratio of NIPAM monomer in poly(NIPAM-co-DMAAPS), the lower the LCST of the polymer. Furthermore, the transition temperature of poly(NIPAM-co-DMAAPS) with a lower NIPAM concentration were not confirmed both in water nor Zn(NO3)2 solution. The more increase the NIPAM concentration used in the preparation, the more increase the polymer viscosity. Moreover, the more increase the adsorption amount of ions onto the gel, the more increase the polymer transmittance as well.